2014
DOI: 10.2147/ijn.s58204
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of zinc oxide nanoparticles binding proteins in rat blood and brain homogenate

Abstract: Nanoparticles (NPs) are currently used in chemical, cosmetic, pharmaceutical, and electronic products. Nevertheless, limited safety information is available for many NPs, especially in terms of their interactions with various binding proteins, leading to potential toxic effects. Zinc oxide (ZnO) NPs are included in the formulation of new products, such as adhesives, batteries, ceramics, cosmetics, cement, glass, ointments, paints, pigments, and supplementary foods, resulting in increased human exposures to ZnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Recently, there have been reports that NPs can reach the brain via blood-brain barrier (BBB) penetration and subsequently cause damage by the induction of oxidative stress, inflammatory responses, and cytotoxicity [1][2][3][4]. It has also been found that ZnONPs could reach the brain after oral administration in animals or translocation along the olfactory nerve pathway [5,6] and may induce the changes in the spatial learning and memory ability of rats by altering the synaptic plasticity [7], and induce toxic effects in the blood and brain [8]. Earlier, ZnONPs have shown toxicity in mice brain tumor cell lines (Neuro-2a) when compared with similar sized particles of Al 2 O 3 , TiO 2 , Fe 3 O 4 , and CrO 3 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been reports that NPs can reach the brain via blood-brain barrier (BBB) penetration and subsequently cause damage by the induction of oxidative stress, inflammatory responses, and cytotoxicity [1][2][3][4]. It has also been found that ZnONPs could reach the brain after oral administration in animals or translocation along the olfactory nerve pathway [5,6] and may induce the changes in the spatial learning and memory ability of rats by altering the synaptic plasticity [7], and induce toxic effects in the blood and brain [8]. Earlier, ZnONPs have shown toxicity in mice brain tumor cell lines (Neuro-2a) when compared with similar sized particles of Al 2 O 3 , TiO 2 , Fe 3 O 4 , and CrO 3 [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more researches have provided evidence that NPs can reach the brain via blood-brain barrier (BBB) penetration or translocation along the olfactory nerve pathway and subsequently cause damage by the induction of oxidative stress, inflammatory responses, and cytotoxicity 12 . It has also been found that ZnO NPs could reach the brain after oral and inhalatrory administration in animals 13 14 , induce the changes in the spatial learning and memory ability of rats by altering the synaptic plasticity 15 , and interact diversely with plasma and brain proteins during inducing their toxic effects in the blood and brain 16 . In vitro studies, ZnO NPs showed the strongest toxicity for mice brain tumor cell lines (Neuro-2a) when compared with similar sized particles of Al 2 O 3 , TiO 2 , Fe 3 O 4 and CrO 3 17 , decreased the activity of mice neural stem cells and human SHSY5Y neuronal cells by inducing DNA damage and cell apoptosis 18 19 , and induced apoptosis in primary cultured astrocytes through JNK signaling pathway 20 .…”
mentioning
confidence: 99%
“…The mitochondrial membrane potential is vital in regulating the electron transport chain and ATP generation. Also, studies have shown that ZnO NPs are predominantly bound tightly to ATP synthase in the brain, causing a mitochondria malfunction and hindering ATP production [33]. Changes in mitochondrial membrane potential have been linked to neurological disorders such as Alzheimer's disease, Parkinson's disease, and Huntington's [34].…”
Section: Discussionmentioning
confidence: 99%